Ultrasound diagnosis of chorionicity and amnionicity in multiple pregnancy - Gil Guevara, Enrique Damián (2015)
Determination of chorionicity and amnionicity by ultrasound is the most important step in the management of multiple pregnancies. This diagnosis should be done in the first trimester of pregnancy not only because less difficulty but because it constitutes the beginning of various steps in the control of these types of pregnancies. It is highly recommended that professionals dealing with this kind of study have the knowledge to assess correctly and promptly chorionicity and amnionicity in multiple pregnancies.